2020
DOI: 10.1111/rssa.12627
|View full text |Cite
|
Sign up to set email alerts
|

On Probability Distributions of the Time Deviation Law of Container Liner Ships Under Interference Uncertainty

Abstract: Container liner shipping is a kind of transportation mode that is operated according to a schedule. Although the goal is to operate container liner ships on time, the actual arrival time and handling time often deviate from the schedule due to uncertain factors. The identification of a proper probability distribution to describe time deviation law will have a significant impact on accurately recognizing the uncertainty of the operation of container liner ships. In view of this problem, this paper discusses the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 28 publications
(35 reference statements)
0
2
0
Order By: Relevance
“…Wu Di et al analyzed the deviation between the actual arrival time of the container liner and the shipping schedule, and proved that the probability of the container liner's arrival at night follows the gamma distribution [4] . Song Yunting et al concluded that the deviation probability of container liner arrival time conforms to Erlang distribution under the conditions of scheduling constraints and disturbance uncertainty [5] .…”
Section: Introductionmentioning
confidence: 99%
“…Wu Di et al analyzed the deviation between the actual arrival time of the container liner and the shipping schedule, and proved that the probability of the container liner's arrival at night follows the gamma distribution [4] . Song Yunting et al concluded that the deviation probability of container liner arrival time conforms to Erlang distribution under the conditions of scheduling constraints and disturbance uncertainty [5] .…”
Section: Introductionmentioning
confidence: 99%
“…In order to mitigate container port congestion when the number of feeders is evidently larger than the number of deep-sea vessels, Jia, et al [44] studied the way to allocate berths to deep-sea vessels and schedule arrivals of feeders. Song and Wang [45] indicated the waiting time of ships is an important indicator of port congestion. The causes of port congestion were not discussed in depth in this article, but the evacuation strategy of vessels after port congestion was mainly analyzed.…”
Section: Introductionmentioning
confidence: 99%